The Zorn property for holomorphic functions - Thai Thuan Quang; Duong Thanh Vy; Le Thanh Hung; Pham Hien Bang (My University, 2017)
The Zorn property for holomorphic functions
Keywords: Zorn property; Holomorphic functions; Mathematical analysis